Broadband microwave absorption performance and theoretical dielectric properties model of hollow porous carbon spheres/expanded polypropylene composite foams. (8th November 2021) - Fan, Digang; Tan, Ruiyang; Wei, Bo; Chen, Ping; Zhou, Jintang
Abstract: Hollow porous carbon spheres (HPCS)/Expanded polypropylene (EPP) composite foams were prepared by rapid expansion of supercritical solution and steam chest molding. Due to the uniform and continuous foam structure, HPCS/EPP foams can maintain better loss ability at lower permittivity. Excellent impedance matching enables them to achieve ultra-broad absorption bandwidth of over 17 GHz. Furthermore, the high frequency dielectric properties of HPCS/EPP foams with unique dual percolation microstructure were described by the Two Exponent Phenomenological Percolation Equation (TEPPE) in a two-step framework. It was revealed that the fitting values of the complex permittivity of the foams with different expansion ratios are in good agreement with the experimental values in the frequency band from 0.5 to 18 GHz. This work introduces a new approach for predicting and optimizing the electromagnetic properties of ternary foamed composites. Graphical abstract: Image 1 Highlights: Hollow porous carbon spheres (HPCS)/EPP foam was prepared by steam chest molding. The lightweight HPCS/EPP foam can achieve broadband microwave absorption. Dielectric properties of composite foam were studied by the effective medium theory.